Conservative prosthetic-periodontal treatment for molar class iii furcation involvement: Case report - Freitas Júnior, Amilcar Chagas [UNESP]; Silva, Antônio Materson; Verde, Marcus Aurélio Rabelo Lima; de Almeida, Erika Oliveira [UNESP] (My University, 2011)
Purpose: The treatment for furcation involvement is a great challenge to the general dentists. Tunneling may be a treatment alternative for class II and III furcation involvements in mandibular molars with large angle separation and great divergence between the mesial and distal roots. This alternative is a conservative treatment that allows a great condition to oral hygiene maintenance by the patient. Thus, the aim of this case report was to describe a conservative and therapeutic treatment modality for the horizontal defect of periodontal tissues in the furcal area with buccal-lingual extension (class III furcation involvement). Case Report: A patient with class III furcation involvement in the first mandibular molar was submitted to root resection and periodontal surgery to expose the clinical crown for the full-coverage restoration with tunnel preparation. Results: The final result of the treatment with tunneled crown was favorable and predictable due to adequate hygiene condition to avoid plaque accumulation and occurrence of root caries. Clinical Significance: A multidisciplinary approach is essential to achieve a correct treatment plan including surgical-periodontal procedures integrated to the prosthetic rehabilitation. Besides, the recommendation for oral hygiene maintenance is essential for the treatment longevity with tunneled crown. © 2011 Nova Science Publishers, Inc.
Keywords: Dental prosthesis; Furcation defects; Molar; Periodontal diseases